Role of poly (ADP-ribose) polymerase-1 and NF-kappaB as potential risk factor in the development of non-small cell lung cancer in Chinese individuals (Bangladesh Journal of Pharmacology, 2018)
The objective of this study was to evaluate the role of poly (ADP-ribose) polymerase-1 (PARP-1) and NF-kappaB as potential risk factor in the development of non-small cell lung cancer in Chinese individuals (n=110) of either gender aged